2002
DOI: 10.1093/humrep/17.7.1746
|View full text |Cite
|
Sign up to set email alerts
|

A prospective study of the effects of female and male caffeine consumption on the reproductive endpoints of IVF and gamete intra-Fallopian transfer

Abstract: This is the first IVF/GIFT study to report any effect of caffeine on live births, gestational age, and multiple gestations. If these findings are replicated, caffeine use should be minimized prior to and while undergoing IVF/GIFT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
77
1
5

Year Published

2003
2003
2017
2017

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(86 citation statements)
references
References 32 publications
3
77
1
5
Order By: Relevance
“…However, there are many environmental factors that may be responsible for observed decreases in sperm quality, independent of age, and that may have significant reproductive consequences, including birth defects (95), cancer (96 -98), and mental disorders (99) in offspring. These environmental insults include cigarette smoking (97, 100), consumption of alcohol (98), and caffeine intake (101). Other environmental factors having a detrimental effect on sperm quality include exposure to industrial chemicals such as phthalates (35) and diagnostic radiation (96).…”
Section: Discussionmentioning
confidence: 99%
“…However, there are many environmental factors that may be responsible for observed decreases in sperm quality, independent of age, and that may have significant reproductive consequences, including birth defects (95), cancer (96 -98), and mental disorders (99) in offspring. These environmental insults include cigarette smoking (97, 100), consumption of alcohol (98), and caffeine intake (101). Other environmental factors having a detrimental effect on sperm quality include exposure to industrial chemicals such as phthalates (35) and diagnostic radiation (96).…”
Section: Discussionmentioning
confidence: 99%
“…Klonoff-Cohen et al reported a higher risk for preterm birth with increasing caffeine intake during pregnancy (15); however, most studies did not find an association between caffeine intake and length of gestation (8,12). Recent dose-response meta-analyses examining the association between prenatal caffeine exposure and risk of adverse pregnancy outcomes indicate that greater caffeine intake during pregnancy may be associated with an increased risk of SA, low birth weight, and small-for-gestational-age infants, but not preterm birth (16,17).…”
Section: Introductionmentioning
confidence: 99%
“…Caffeine intake was not significantly associated with other outcomes. This was the first IVF/GIFT study to report any effect of caffeine on live births, gestational age, and multiple gestations and if these findings are replicated, caffeine use should be minimized prior to and while undergoing IVF/ GIFT (Klonoff-Cohen et al 2002).…”
Section: Caffeine In Assisted Reproductive Techniquesmentioning
confidence: 89%